An investigation into the damage development and residual strengths of open-hole specimens in fatigue. (February 2015) - Nixon-Pearson, O.J.; Hallett, S.R.
Abstract: An extensive experimental program was carried out to investigate and understand the sequence of damage development throughout the life of open-hole composite laminates loaded in tension–tension fatigue. Quasi-isotropic carbon/epoxy laminates, with stacking sequence [452 /902 /−452 /02 ]S, [45/90/−45/0]2S and [45/90/−45/0]4S were examined. These were selected on the basis that under quasi-static loading the [452 /902 /−452 /02 ]S configuration exhibited a delamination dominated mode of failure whilst the [45/90/−45/0]2S and [45/90/−45/0]4S configurations showed a fibre dominated failure mode, previously described as "pull-out" and "brittle" respectively. Specimens were fatigue loaded to 1 × 10 6 cycles or catastrophic failure, which ever occurred first. A number of tests were interrupted at various points as the stiffness dropped with increasing cycles, which were inspected using X-ray computed tomography (CT) scanning. A static residual strength program was carried out for run-out specimens of each configuration.